(untitled) (Journal of Interdisciplinary Insights, 2024)
The role of academic emotions in influencing students’ learning experiences and outcomes is increasingly recognized, particularly as artificial intelligence (AI) becomes more integrated into educational settings. Understanding how these emotions interact with AI is essential for enhancing student performance.While existing research has established the general effects of academic emotions on performance, the specific impacts of AI on these emotions and their subsequent influence on academic outcomes remain under-explored. This study employs a mixed-methods approach, involving 120 translation students from three universities that utilize AI-driven learning systems. Participants completed a modified Academic Emotions Questionnaire and provided qualitative reports detailing their experiences with AI tools. Their academic performance was collected. Regression analysis reveals that positive emotions—anticipation, joy, and curiosity—significantly predict academic performance in AI-enhanced environments. Additionally, topic modeling of students’ reports identifies key themes such as reduced cognitive load , access for academic resources, immediate feedback and personalized learning, indicating that AI tools positively influence academic emotions and performance. The findings underscore the importance of designing AI systems that foster positive academic emotions, thereby improving educational outcomes. This research highlights the need for further exploration into the emotional dynamics of AI in education to support both cognitive and emotional development in students.